Perspective on Aggregation-induced Emission (AIE) Materials for Pathogen Detection - Zhou, Chengcheng; Zhu, Yaping; Guan, Weijiang (Current Analytical Chemistry, 2023)
The rapid and accurate identification of pathogens plays a crucial role in clinical practice, which helps to prevent, control, and treat pathogenic infections at the initial stage. The current available technologies for pathogen detection appear to be inadequate in dealing with cases such as COVID-19. More importantly, the frequent emergence of drug-resistant bacteria is gradually rendering the existing therapeutic options ineffective. Efforts are urgently required to focus on the development of diagnostic systems for point-of-care (POC) detection and high-throughput pathogen identification. Since 2001, a new class of aggregation-induced emission luminogens (AIEgens) with good photostability, high sensitivity, and improved signal-to-noise ratio has emerged as powerful fluorescent tools for various biosensing and cell imaging. Based on the unique fluorescence of AIEgens that becomes stronger upon aggregation, naked-eye detection in turn-on mode has gained a speedy development. A timely overview can not only provide a summary of the advances and challenges of AIEgens in pathogen detection but also offer systematic ideas for future developments. There are also expectations for in-depth interdisciplinary research in the field of analytical chemistry and microbiology.
Keywords: aggregation-induced emission